Penerapan Layanan Konseling Kelompok Dalam Meningkatkan Minat Belajar Siawa di SMP Frater Don Bosco Tomohon - Silitonga, Mora; Mangantes, Meisie L.; Kasenda, Rinna Y. (Jurnal Ilmiah Wahana Pendidikan, 2026)
This study aims to determine how the implementation of group counseling services can improve students' learning interest at SMP Frater Don Bosco Tomohon. Learning interest is one of the important factors that influence students' success in the education process. Lack of learning interest can impact low academic achievement, motivation, and student participation in learning activities. This study uses Guidance and Counseling Action Research (GCAR/PTBK in Indonesian). The research subjects are students with low levels of learning interest based on the results of the initial questionnaire. Data collection techniques were carried out through observation, questionnaires, and documentation. Group counseling services were provided in several sessions with materials designed to raise awareness, motivation, and students' learning responsibility. The results showed a significant increase in students' learning interest after participating in group counseling services. This is evident from the increase in learning interest questionnaire scores before and after the intervention. Thus, it can be concluded that group counseling services are effective in improving students' learning interest at SMP Frater Don Bosco Tomohon